Distinct immune composition in lymph node and peripheral blood of CLL patients is reshaped during venetoclax treatment - Iris de Weerdt; Tom Hofland; Renate de Boer; Johan A. Dobber; Julie Dubois; Denise van Nieuwenhuize; Mehrdad Mobasher; Fransien de Boer; Mels Hoogendoorn; Gerjo A. Velders; Marjolein van der Klift; Ester B.M. Remmerswaal; et al. (Blood Advances, 2019)
Abstract: Morbidity and mortality due to immunosuppression remain among the foremost clinical challenges in chronic lymphocytic leukemia (CLL). Although immunosuppression is considered to originate within the lymph node (LN) microenvironment, alterations in T and natural killer (NK) cells have almost exclusively been studied in peripheral blood (PB). Whereas chemoimmunotherapy further deteriorates immune function, novel targeted agents like the B-cell lymphoma 2 inhibitor venetoclax potentially spare nonmalignant lymphocytes; however, the effects of venetoclax on nonleukemic cells have not been explored. We address these unresolved issues using a comprehensive analysis of nonmalignant lymphocytes in paired LN and PB samples from untreated CLL patients, and by analyzing the effects of venetoclax-based treatment regimens on the immune system in PB samples from previously untreated and relapsed/refractory patients. CLL-derived LNs contained twice the amount of suppressive regulatory T cells (Tregs) and CLL supportive follicular T helper (Tfh) cells compared with PB. This was accompanied by a low frequency of cytotoxic lymphocytes. The expression of PD-1 by CD8+ T cells was significantly higher in LN compared with PB. Venetoclax-based treatment led to deep responses in the majority of patients, but also to decreased absolute numbers of B, T, and NK cells. Tfh cell, Treg, and PD-1+ CD8+ T cell numbers were reduced more than fivefold after venetoclax-based therapy, and overproduction of inflammatory cytokines was reduced. Furthermore, we observed restoration of NK cell function. These data support the notion that the immunosuppressive state in CLL is more prominent within the LN. Venetoclax-based regimens reduced the immunosuppressive footprint of CLL, suggesting immune recovery after the elimination of leukemic cells.